Transforming the sheep and goat industry through dispersed community based breeding and centralized management - Getachew, Tesfaye; Rischkowsky, Barbara A.; Rekik, Mourad; Santos, Bruno; Tesfahun, Girma; Belay, Berhanu; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2022)
Transforming the sheep and goat industry through dispersed community-based breeding and centralized management. Presentation at 30th ESAP Conference. September 15-17th.